Bacillus toyonensis SAU-19 and SAU-20 Isolated From Ageratina adenophora Alleviates the Intestinal Structure and Integrity Damage Associated With Gut Dysbiosis in Mice Fed High Fat Diet - Okyere, Samuel Kumi; Wen, Juan; Cui, Yujing; Xie, Lei; Gao, Pei; Zhang, Ming; Wang, Jianchen; Wang, Shu; Ran, Yinan; Ren, Zhihua; Hu, Yanchun (Frontiers in Microbiology, 2022)
This study was performed to identify potential probiotic endophytes from Ageratina adenophora and evaluate their ameliorating effects on gut injury and integrity damage associated with microbiota dysbiosis in mice fed high fat diet. Using morphological and biochemical tests, and 16S rRNA gene sequencing technique, two bacteria endophytes were identified as strains of Bacillus toyonensis and were named Bacillus toyonensis SAU-19 (GenBank No. MW287198) and Bacillus toyonensis SAU-20 (GenBank No. MW287199). Sixty (60) mice were divided into 5 groups, group 1 was the negative control fed normal diet (NS), group 2 was fed High fat diet (HF), Group 3 was fed High fat diet +106 Lactobacillus rhamnosus (LGG), group 4 was fed High fat +106 Bacillus toyonensis SAU-19 and group 5 fed High fat diet+106 Bacillus toyonensis SAU-20. After 35 days, histological and immunohistochemistry examination were performed in the ileum tissues. Furthermore, DAO and antioxidants activities were measured in serum, mRNA expressions of tight junction proteins (occludin and ZO-1) and inflammation related cytokines (IL-1β, TFN-α, IL-2, IL-4 and IL-10) in the ileum tissues as well as sIgA levels and total bacteria (E. coli, Salmonella, Staphylococcus and Lactobacillus) in the small intestine and caecum content. The results showed an increase in the DAO activity, oxidative stress parameter (MDA), pro-inflammation cytokines (IL-1β, TFN-α, IL-2), reduce immunity (sIgA), and destroyed intestinal structure and integrity (reduce tight junction proteins) in the high fat diet group and this was associated with destruction of the gut microbiota composition (increasing pathogenic bacteria; E. coli, Salmonella, Staphylococcus and reducing beneficial bacteria, Lactobacillus spp) in mice (P<0.05). However, the administration of Bacillus toyonensis SAU-19 and SAU-20 reverted these effects. Our findings indicated that, Bacillus toyonensis SAU-19 and SAU-20 isolated from A. adenophora could prevent the excess weight gain from high fat diet feeding, improved antioxidant status and alleviated the intestine integrity damage as well as reduce the population of enteric bacteria such as E. coli, Salmonella and S. aureus and increasing the population of beneficial bacteria such as Lactobacillus in the gut of mice fed high fat diet, therefore, can serve as a potential probiotic in humans and animals.